시호(Bupleuri Radix)분말이 고콜레스테롤 급여 흰쥐의 체지질구성 및 TBARS량에 미치는 영향 - 이준무; Lee Jun Mu; 이은; Lee Eun; 최무영; Choe Mu Yeong (대한본초학회지(본초분과학회지), 2000)
Effects of powdered siho(Bupleuri Radix) on lipid composition and TBARS were investigated in rat fed high cholesterol. Plasma total cholesterol showed a tendency to increase in cholesterol group(P<.OS). However, in the cholesterol group, contents of serum total cholesterol showed no significantly different among treatments(P>.OS). Plasma HDL-cholesterol and triglyceride contents showed no significantly different among treatments(P>.OS). Liver total cholesterol showed a tendency to increase in cholesterol group, however these values showed no significantly different among all the treatments(P>.05). Liver triglyceride contents showed no significantly different among all the treatments(P>.05). Contents of plasma and liver TBARS were high (Pc.05) in control group fed high cholesterol only. however these values were lower by powdered siho(Bupleuri Radix) feeding. Glutathione peroxidasc activity showed low in control group fed high cholesterol only(P<.OS), however these values showed a tendency to increase(P<.OS) by powdered ailio(Bup1euri Radix) feeding